How to promote STEM competencies through design - Nichols, Kim; Musofer, Reshma; Haynes, Michele (Frontiers in Education, 2022)
This study explored the impact of a community of inquiry on Science, Design Technology and Mathematics curriculum competencies of 159 Year six students as they carried out a design task. A quasi-experimental design was employed with both qualitative and quantitative analyses. A community of inquiry approach was adopted by the teachers (n=3) in the experimental group but not by teachers (n=4) in the comparison group. Both groups carried out a unit of work on electricity culminating in a design challenge in small collaborative groups. The results showed that the experimental group (n=65) demonstrated significantly greater instances and a broader range of competencies across the design task as well as significantly higher learning gains than their comparison group (n=95) peers.